2003
DOI: 10.1540/jsmr.39.47
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Cyclic Nucleotide Regulation of MBCQ-induced Relaxation of Rat Ileal Smooth Muscle.

Abstract: The effects of the type V phosphodiesterase (PDE V) inhibitors, MBCQ, zaprinast and dipyridamole, on the relationship between relaxation and cyclic nucleotide content were investigated in rat ileal smooth muscle. Each of MBCQ (0.01-10 µM), zaprinast (0.1-100 µM) and dipyridamole (0.1-100 µM) inhibited carbachol (CCh; 10 µM)-induced contractions in a concentration-dependent manner. When compared with the concentrations of these agents producing 50% relaxation (IC50) of CCh-induced contraction, MBCQ was 14-20 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, at a concentration that induced half-maximum relaxation, Ro20-1724-increased cAMP content was less than that of the other inhibitors. We reported that MBCQ, a selective PDE 5 inhibitor, inhibits muscle contraction without changes in cAMP and cGMP content in ileal smooth muscle [12]. Therefore, it seems that Ro20-1724-induced relaxation may be partially involved in the cAMP-and cGMP-independent mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…However, at a concentration that induced half-maximum relaxation, Ro20-1724-increased cAMP content was less than that of the other inhibitors. We reported that MBCQ, a selective PDE 5 inhibitor, inhibits muscle contraction without changes in cAMP and cGMP content in ileal smooth muscle [12]. Therefore, it seems that Ro20-1724-induced relaxation may be partially involved in the cAMP-and cGMP-independent mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…Phosphodiesterase 5, the target of sildenafil, with other components of the cGMP signalling cascade is primarily located in smooth muscle tissues, including the gastrointestinal tract. 4,5 This type of drug produces PDE5 inhibition, increasing intracellular concentrations of cGMP and enhancing NO-induced smooth muscle relaxation. 24 Therefore, substances that increase cellular levels of cGMP may lead to a reduced smooth muscle tone and inhibited responsiveness to contractile agonists.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The smooth muscle cells of the gastrointestinal tract also contain cGMP and PDE5 enzyme. 4,5 Once inhibitory neurotransmitters, such as nitric oxide (NO) or atrial natriuretic peptide, are released, they increase intracellular cGMP levels, which decrease cytosolic Ca 2+ content, and smooth muscle relaxation occurs. 6,7 Recent evidence indicates that sildenafil modifies gastrointestinal motility both in animals and humans.…”
Section: Introductionmentioning
confidence: 99%